STRATEGI ASISTENSI MENGAJAR DALAM MENINGKATKAN PEMAHAMAN JURNAL UMUM DI SMA TARSISIUS II JAKARTA - Wieleycia Terence; Merry Susanti (Jurnal Serina Abdimas, 2025)
The teaching assistance program in educational institutions is an activity carried out by students to teach in educational units under the guidance of lecturers and teachers, which is one of the Merdeka Belajar Kampus Merdeka (MBKM) programs. This program aims to improve students' teaching skills, broaden their academic knowledge and experience, and assist schools during the learning process. To achieve these objectives, the Tarumanagara University assistance team initiated an accounting teaching program at Tarsisius II High School in Jakarta. The selection of partners was based on the declining and low level of student interest in accounting, so it is hoped that this program will help increase student enthusiasm and assist students who have difficulty understanding accounting concepts, especially general journals. The learning and teaching process were conducted offline in an interesting, innovative, and interactive way from August to October. These activities included providing in-depth explanations of general journals, giving practice questions as a form of hands-on practice in recording general journals, giving quizzes to assess students' understanding of general journals, and holding question and answer sessions. This program can benefit all parties, especially schools, by increasing students' understanding and interest in accounting material and helping teachers deliver material in new ways. For students, this program can be a means for them to hone their teaching skills and apply accounting knowledge in a practical way. Thus, the assistance program is expected to have a positive impact on improving the quality of education, especially in the field of accounting. Program asistensi mengajar di satuan pendidikan adalah kegiatan yang dilakukan mahasiswa untuk mengajar di satuan pendidikan di bawah bimbingan dosen dan guru yang merupakan salah satu dari program Merdeka Belajar Kampus Merdeka (MBKM). Program ini bertujuan untuk meningkatkan kemampuan mahasiswa dalam mengajar, memperluas wawasan dan pengalaman akademik yang dimiliki, serta membantu pihak sekolah selama proses pembelajaran. Untuk mencapai tujuan tersebut, tim asistensi Universitas Tarumanagara menginisiasi program mengajar akuntansi di SMA Tarsisius II Jakarta. Pemilihan mitra didasarkan pada minat siswa terhadap akuntansi yang terus menurun dan tergolong rendah, sehingga terlaksananya program ini diharapkan dapat membantu meningkatkan antusiasme siswa dan membantu siswa yang mengalami kesulitan dalam memahami konsep akuntansi secara mendalam terutama jurnal umum. Proses pembelajaran dan pengajaran dilakukan secara luring dengan cara yang menarik, inovatif dan interaktif yang berlangsung selama Agustus hingga Oktober. Kegiatan ini meliputi memberikan penjelasan yang mendalam mengenai jurnal umum, memberikan soal latihan sebagai bentuk praktik langsung dalam mencatat jurnal umum, memberikan soal quiz untuk menilai pemahaman siswa mengenai jurnal umum, dan membuka sesi tanya jawab. Program ini dapat memberikan manfaat kepada seluruh pihak, terutama pihak sekolah berupa peningkatan pemahaman dan minat siswa terhadap materi akuntansi, dan membantu guru dalam menyampaikan materi dengan cara yang baru. Bagi mahasiswa, program ini dapat menjadi sarana bagi mahasiswa untuk mengasah kemampuan mengajar, dan menerapkan ilmu akuntansi secara praktis. Dengan demikian, program asistensi diharapkan mampu memberikan dampak positif dalam peningkatan kualitas pendidikan terutama di bidang akuntansi.